Characterization of an artisanal fishery in Argentina using the social-ecological systems framework. Issue 1 (March 2017) - London, Silvia; Rojas, Mara L.; Ibáñez Martin, María M.; Scordo, Facundo; Cisneros, M. Andrea Huamantinco; Bustos, M. Luján; Perillo, Gerardo M.E.; Piccolo, M. Cintia
Institutional Analysis and Development (IAD) studies how institutions (the rules of the game of a society) determine the performance of a social-economic system. Elinor Ostrom extends the institutional analysis to the collective action for a particular case, the study of the social-ecological systems (SESs) (Ostrom 1990 ). Any group that attempts to manage a common resource (e.g. aquifers, pastures) for optimal sustainable production must solve a set of problems in order to create institutions to facilitate collective action. Some evidences show that following a set of design principles in creating institutions can lead to overcome these problems. The aim of the paper is to apply the SES framework to an artisanal fishery community in Argentina in order to: 1) describe the principal features, key variables and relations of the small-scale fishery system; 2) detect the principal drivers of a potential common-management and the leading detractors from the current communal performance; and 3) analyze the possibility that a self-governing for sustainable fishery may appear. Several drivers for potential common-management and some detractors from the current common performance are summarized. Artisanal fishery SES is currently at a bifurcation point. A common historical and cultural root, the presence of leaderships, the relevance of local knowledge, the dependence on the resource to sustainable livelihoods and the threat of big-scale fisheries area have generated incentives to collective-action. But, simultaneously, internal conflicts are the most important barrier for an integrated community-based management. The heterogeneity among actors and the relevant external conditions have resulted in two groups diverging in their self-organization. The work is framed by the project COMET-LA (COmmunity-based Management of Environmental challenges in Latin America; European Commission's Seventh Framework Programme of Research and Development), which aims to identify sustainable community-based governance for the management of natural resources that can be used in different social-ecological systems in a context of climate change and increasing competition in the use of resources.